Identification of Staphylococcus aureus in ground beef sold in municipalities of Guaribas Valley, in the State of Piauí (Research, Society and Development, 2020)
This research aimed to identify S. aureus in ground beef sold in municipalities of Valley do Guaribas, in the state of Piauí. 50 dev of ground beef was collected, acquired in the markets and public butchers in the cities surveyed. Weighed 25g of each sample and each sample was transferred to 0.1% Buffered Peptone Water, where homogenization and identification of the samples were carried out in an oven at 37 ° C for 24 hours. Petri dishes were inoculated in Petri dishes containing Baird-Parker Agar (BP) and incubated in this oven (in an inverted position) for 48 hours at 37 ° C. Typical S. aureus colonies were inoculated in test tubes containing Brain Heart Infusion Broth (BHI) and incubated at 37 °C for 24 hours. Finally, it was sown, in Petri dishes containing Agar Salt Mannitol, as, that dissipate turbids in the BHI broth and incubated for the same temperature and temperature time. For the identification of Staphylococcus aureus, suspicious colonies were used, and the following biochemical tests were performed: Gram stain, catalase test and coagulase test. After the execution of the methodology, it was found that of the 50 evaluated, 32 (64%) showed a positive result for cultures of S. aureus after indicating suspicions of the presence of colonies on mannitol agar. The high number of contaminated can be explained by several factors that involve its entire production chain until the moment of their commercialization, promoting an increasing number of cases of food poisoning by toxins formed in food due to the presence of this pathogen.